Benchmarking In Tesol : Benchmarks Of Management Of Learning And Teaching - Parveen, Kaur; Arif, Jawaid (Publications International Lahore, Pakistan, 2019)
Benchmarking is a very common real-life function and happens every moment unnoticed, this article, as a result of the research into TESOL (Teaching of English to Speakers of Other Languages), argues for benchmarking and auditing to help develop quality education/TESOL. In the research many benchmarks were drawn from a detailed comparative analysis and synthesis of extant literature, leading to the development and codification of quality characteristics and standards for an area. This provided TESOL Quality Audit framework that can be a prelude to improve staff, curriculum, and institutional development. As the approach was used in research in TESOL, the context of the research is provided, as is a worked example drawn from the extensive literature review on the management of TESOL in the classroom. Possible implications for staff development and curriculum improvement are identified.